Evaluating the Effectiveness of I-NEED Program: Improving Nurses’ Detection and Management of Elder Abuse and Neglect—A 6-Month Prospective Study - Mohd Mydin, Fadzilah Hanum (Journal of interpersonal violence, 2022)
Elder abuse and neglect (EAN) goes largely unrecognized and underreported globally by health care professionals. Despite acknowledging their role to intervene elder abuse, health care professionals lacked knowledge and skills in this issue. This is a single-blinded, three-armed, cluster randomized controlled trials aimed to evaluate the effectiveness of the face-to-face Improving Nurses’ dEtection and managEment of elDer abuse and neglect (I-NEED) intensive training program and I-NEED educational video in improving primary care nurses’ knowledge, attitude, and confidence to intervene EAN; 390 primary care nurses were randomized equally into two intervention groups—ITP group (intensive training program) and ITP+ group (intensive training program and educational video)—and a control group. The knowledge, attitudes, and confidence to intervene EAN were measured using questionnaires at four intervals during 6-month follow-up. A total of 269 primary care nurses participated in this study. There was a significant increase in knowledge, attitude, and confidence to intervene EAN immediately post intervention observed in both intervention groups compared to the control group (p < .001). At the end of sixth month, there was an increase of knowledge favoring ITP group than the ITP+ group (p < .001). There is, however, no significant difference in attitude score between ITP and ITP+ group. There is a significant difference of confidence to intervene among the participants between both intervention groups with ITP+ participants reporting higher scores post intervention (p < .05). An intensive training module improved the knowledge, attitude, and confidence to intervene EAN. Other co-existing barriers for abuse victims getting help, resources, policy, and law of EAN need further highlights.